AlcaliNObacter (2023)
In a collaborative project focused on enhancing the well-being of rural populations in Colombia, thorough observations and interviews were conducted. Medical centers like Profamilia and the Juan N Corpas clinic were examined, along with interviews with healthcare professionals. Additionally, individuals living near the La Copa dam in Boyaca were interviewed to validate the need for a product. The team identified a pressing need for improving primary care for sharp wounds in rural areas. Wound infections contribute significantly to the delayed healing of chronic open wounds and increase hospital costs. Detecting and treating these infections can lead to a 10% to 20% rise in expenses and extended hospital stays. While complete elimination of wound infections is not feasible, reducing the infection rate to a minimum level can greatly benefit patients' comfort and efficient use of medical resources. Therefore, offering a temporary solution to seal sharp wounds becomes crucial for preventing infections and improving people's quality of life in rural areas of Colombia. The product developed for addressing this pressing need is called AlcaliNObacter. It is a biocompatible adhesive and waterproof dressing that contains a hydrogel. AlcaliNObacter is designed to be included in Type A first aid kits as an immediate solution for isolating wounds when suturing is not available. The inclusion of a pH indicator allows for the identification of bacterial infections, while the hydrogel, composed of chitosan and 1% acetic acid, promotes tissue healing and provides antimicrobial properties. Additionally, the product incorporates a broad-spectrum antibiotic to minimize the risk of infections from various bacteria. AlcaliNObacter effectively shields the wound from the environment and prevents infection until a trained healthcare professional is able to suture the patient.